Can coaches predict long-term career attainment outcomes in adolescent athletes?. Issue 3 (June 2019) - Cripps, Ashley J; Hopper, Luke S; Joyce, Christopher
Coaches' subjective perceptions of an athlete's career potential play an important role in the identification and subsequent selection of talented adolescents into or out of development pathways. However, evidence suggests that these perceptions may be biased by variations in athlete maturity. The primary aim of this study was to examine the predictive accuracy of development pathway coaches' perceptions when tasked with identifying adolescent athlete's long-term potential within the Australian Football talent pathway. A secondary aim was to explore if the maturational status of adolescent athletes influenced the accuracy of coaches' long-term career attainment predictions. This observational study initially recruited adolescent athletes (n = 264) and their coaches (n = 9) from teams involved in a state-based Australian Football competition. At the initial testing sessions, estimates for biological maturity were undertaken for all athletes and coaches were asked to rate the perceived long-term career attainment potential of their athletes via a questionnaire. Four years after this initial questionnaire, the research team retrospectively examined each athlete's highest level of competition attained. Coaches correctly predicted the level of career attainment for 63% of athletes, demonstrating a fair level of agreement (κ = 0.25, 95% CI = −0.16–0.35, p < 0.001) between coach perception and actual career progression outcomes. The coaches' greatest level of predictive accuracy was for late maturing athletes (79% accuracy), while the poorest was for the early maturing athletes (52% accuracy). The findings of this study highlight the complexity associated with correctly identifying athletes with long-term performance potential at early stages of development pathways.